Theoretical Study on the Extraction of Alkaline Earth Salts by 18-Crown-6: Roles of Counterions, Solvent Types and Extraction Temperatures - Saprizal Hadisaputra; Lorenz R Canaval; Harno Dwi Pranowo; Ria Armunanto (Universitas Gadjah Mada, 2014)
The roles of counterions, solvent types and extraction temperatures on the selectivity of 18-crown-6 (L) toward alkaline earth salts MX2 (M = Ca, Sr, Ba; X = Cl-, NO3-) have been studied by density functional method at B3LYP level of theory in gas and solvent phase. In gas phase, the chloride anion Cl- is the preference counterion than nitrate anion NO3-. This result is confirmed by the interaction energies, the second order interaction energies, charge transfers, energy difference between HOMO-LUMO and electrostatic potential maps. The presence of solvent reversed the gas phase trend. It is found that NO3- is the preference counterion in solvent phase. The calculated free energies demonstrate that the solvent types strongly change the strength of the complex formation. The free energies are exothermic in polar solvent while for the non polar solvent the free energies are endothermic. As the temperature changes the free energies also vary where the higher the temperatures the lower the free energy values. The calculated free energies are correlated well with the experimental stability constants. This theoretical study would have a strong contribution in planning the experimental conditions in terms of the preference counterions, solvent types and optimum extraction temperatures.